New records of Streblidae (Diptera: Hippoboscoidea) for Mexico - Cuxim-Koyoc, Alan; Reyes-Novelo, Enrique; Macswiney, M. Cristina; Aguilar-Rodríguez, Pedro A. (Revista Colombiana de Entomología, 2016)
Trichobius brennani and Anatrichobius scorzai are reported as two new records of ectoparasite bat flies (Diptera: Streblidae) from Mexico. Six new species are recorded for the state of Veracruz as well, having been collected on hosts belonging to the families Phyllostomidae and Vespertilionidae. According to these records, the list of Streblidae for Mexico increases to 51 species, 23 of which are distributed in the state of Veracruz.